SOCIAL DIMENSIONS ON POLITENESS STRATEGIES OF REFUSALS USED BY AMBONESE AND AMERICAN - Azwan (Universitas Samudra, 2021)
The aims of this study were to identify the politeness strategies used by Ambonese and Americans in refusing requests, as well as the effects of social relationships. A descriptive qualitative approach was used in the study. The data of American conversations were collected from youtube.com and direct observation by recording conversations between interlocutors by 20 respondents of Ambonese in any situation. The data was analyzed and classified using six politeness systems by Yassi, and politeness strategies by Brown and Levinson. The results show that in interactions between strangers, Ambonese people tend to use a bald on record strategy, which is frequently combined with a negative politeness strategy, whereas Americans tend to use a negative politeness strategy, which includes expressing apology followed by a direct expression of refusal or using off-record strategy. In an intimate relationship, Ambonese people tend to use positive politeness strategies, whereas Americans tend to use off-record strategies and negative politeness strategies. In a hierarchal relationship, Ambonese tend to use negative politeness strategies by inferior to superior person, while Americans tend to use negative politeness strategies or off record strategies. Culturally, Ambonese people were influenced by local wisdom to maintain solidarity in responding and addressing, which is called Pela Gandong, whereas Americans were influenced by the freedom to express themselves.